Smart Farming Integrating Conservation Agriculture, Information Technology, and Advanced Techniques for Sustainable Crop Production - Danish, Subhan; Ali, Hakoomat; Datta, Rahul (IntechOpen, 2023)
Smart Farming - Integrating Conservation Agriculture, Information Technology, and Advanced Techniques for Sustainable Crop Production is a timely and comprehensive volume that explores the latest advances and opportunities in an emerging field. The book brings together experts from various disciplines to discuss the principles, practices, and technologies of smart farming, and their potential for sustainable agriculture. Topics include the adoption of conservation agriculture, information technology drivers in smart farming management systems, physiological breeding, and nanotechnology applications in smart farming. This book is intended for researchers, policymakers, and practitioners in the field of agriculture who are interested in exploring the latest developments in smart farming and its potential for enhancing crop production, reducing environmental impact, and increasing farmers' profits.